A novel mechanism for user-friendly and self-activated microdroplet generation capable of programmable control. Issue 16 (28th June 2018) - Jiang, Yangyang; Du, Lin; Li, Yuanming; Mu, Quanquan; Cui, Zhongxu; Zhou, Jia; Wu, Wenming
Abstract : The real-time continuous-flow PCR inside a 3D spiral microchannel is realized by a novel self-activated microdroplet generation/transport mechanism. Abstract : Unlike conventional approaches that require bulky and expensive pumping equipment, herein, we present a simple method for self-activated microdroplet generation and transport inside a long microchannel. The high gas-pressure in the syringes is used to provide the built-in power of self-priming so that the continuous phase and the dispersed phase are sequentially automated into the generator junction to produce stabilized droplets. The volume ratio between the aqueous and oil phases can be adjusted in a flexible way by accurately controlling the volume of the compressed air in the two syringes, and a novel self-activated micropumping mechanism is introduced to explain this phenomenon. Through the flow rate test inside the microchannels under different conditions, it is found that the flow rate of microdroplets inside the Teflon microchannel is highly stable. As a proof of concept, this novel micropump is applied for a 3D spiral chip for flow through PCR. It is demonstrated that this self-activated micropump is acceptable for droplet-based continuous flow microfluidic PCR with the thermal-cycle controlled by a single thermostatic heater, while the real-time (RT) fluorescence signal is comparable to a commercial qPCR cycler. This self-activated, portable, and controllable droplet generator would extend the droplet-based applications to in-field analysis and facilitate the exploitation of droplet microfluidics by non-technical users.